Hematology profile of kissing gourami Helostoma temminckii infected with Aeromonas hydrophila bacteria - Adna Sumadikarta; Sata Yoshida Srie Rahayu; Sri Nuryati (Jurnal Akuakultur Indonesia, 2026)
The kissing gourami (Helostoma temminckii) is an important commodity in aquaculture, but its susceptibility to bacterial infections such as Aeromonas hydrophila can hinder production. This study aims to investigate the hematological profile of kissing gourami (Helostoma temminckii) with an average length of 8.00 ± 1.00 cm and weight of 10.00 ± 1.00 g, following intramuscular injection of Aeromonas hydrophila at a dose of 10⁶ CFU/mL.Evaluations were conducted on survival rate, hematological parameters such as total erythrocytes, total leukocytes, hemoglobin levels, and hematocrit, as well as phagocytic activity, respiratory burst, and lysozyme activity. Infection with A. hydrophila caused a decrease in erythrocytes and hemoglobin, and an increase in leukocytes, phagocytic activity, respiratory burst, and lysozyme activity. The survival rate dropped to 47.5% in the treatment group, while the control group showed 100% survival. The conclusion is, infection of Aeromonas hydrophila significantly affects the immune response of kissing gourami, characterized by an decrease in erythrocyte count and hemoglobin levels in the treatment group. However, phagocytic activity, respiratory burst, and lysozyme levels consistently decreased in infected fish. Keywords: Aeromonas hydrophila, hematology, kissing gourami, pathogenicity   Abstrak Ikan tambakan (Helostoma temminckii) merupakan komoditas penting dalam budidaya perikanan, namun kerentanannya terhadap infeksi bakteri seperti Aeromonas hydrophila dapat menghambat produksi. Penelitian ini bertujuan untuk mengkaji profil hematologi ikan tambakan (Helostoma temminckii) dengan panjang rata-rata 8,00 ± 1,00 cm dan bobot 10,00 ± 1,00 g setelah disuntik intramuskular Aeromonas hydrophila dengan dosis 10⁶ CFU/mL. Evaluasi dilakukan terhadap tingkat kelangsungan hidup, parameter hematologi seperti jumlah eritrosit total, leukosit total, kadar hemoglobin, dan hematokrit, serta aktivitas fagositosis, respiratory burst, dan aktivitas lisozim. Infeksi A. hydrophila menyebabkan penurunan jumlah eritrosit dan kadar hemoglobin, serta peningkatan jumlah leukosit, aktivitas fagositosis, respiratory burst, dan aktivitas lisozim. Tingkat kelangsungan hidup menurun menjadi 47,5% pada kelompok perlakuan, sedangkan kelompok kontrol menunjukkan kelangsungan hidup 100%. Kesimpulannya, infeksi Aeromonas hydrophila secara signifikan memengaruhi respons imun ikan kissing gourami, yang ditandai dengan penurunan jumlah eritrosit dan kadar hemoglobin, serta peningkatan aktivitas fagositosis, respiratory burst, dan kadar lisozim pada ikan yang terinfeksi. Kata kunci: Aeromonas hydrophila, hematologi, ikan tambakan, patogenisitas